Advance Care Planning Program and the Knowledge and Attitude Concerning Palliative Care. Issue 3 (27th May 2019) - Sung, Huei-Chuan; Wang, Shu-Chen; Fan, Sheng-Yu; Lin, Chia-Ying
ABSTRACT: Objectives : The study aimed to evaluate the effects of an advance care planning (ACP) program on knowledge and attitudes concerning palliative care, and decisions regarding DNR orders in the older residents in a long-term care institution. Methods : A quasi-experimental design was used. Participants were cognitively unimpaired older residents in a long-term care institution in Taiwan. The experimental group ( n  = 29) received the intervention including an individual interview using an ACP handbook and a group patient education; whereas the control group ( n  = 28) received the group patient education only. Results : There were significant positive effects of the ACP program on understanding of DNR and palliative care, willingness to sign a DNR order, and knowledge of and attitude towards palliative care; however, there was no significant effect on willingness to receive palliative care. Six participants signed the DNR order after the intervention compared to none in the control group. Conclusions : The ACP program can improve knowledge and attitudes towards palliative care in older residents in long-term care institutions. Clinical Implications : The ACP program could incorporate multiple components, including individual interview using ACP handbook and group patient education, and address knowledge and attitudes towards palliative care.